2022
DOI: 10.1186/s40814-022-00997-2
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid high-intensity interval training using functional electrical stimulation leg cycling and arm ski ergometer for people with spinal cord injuries: a feasibility study

Abstract: Aim The aim was to assess safety and feasibility of Hybrid High-Intensity Interval Training (HIIT) using Functional Electrical Stimulation (FES) leg cycling and arm ski ergometer in people with Spinal Cord Injuries (SCI). Method Eight outpatients (mean age 42.8 years; 7 men) with stable SCI paraplegia (mean 14.5 years since injury) participated in hybrid HIIT (90% peak watts; 4 × 4–min intervals), three times a week (over 8 weeks). Primary outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 77 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…Safety is therefore mandatory for any diagnostic method in this population. As previously reported, 22 an acute cardiac event during FES‐cycling is an objective safety parameter to stop the procedure. Besides the huge electrical charge, the high intensity and large pulse width were safely used during the diagnostic method.…”
Section: Discussionmentioning
confidence: 89%
“…Safety is therefore mandatory for any diagnostic method in this population. As previously reported, 22 an acute cardiac event during FES‐cycling is an objective safety parameter to stop the procedure. Besides the huge electrical charge, the high intensity and large pulse width were safely used during the diagnostic method.…”
Section: Discussionmentioning
confidence: 89%
“…Likewise, Janssen and Pringle [ 70 ] reported “lightheadedness in some subjects” and Gibbons and colleagues [ 91 ] stated that “a number of participants showed some level of autonomic dysreflexia during the FES response test”, but both studies did not quantify further. Vestergaard and colleagues [ 92 ] reported adverse events relating to “slight non-persisting pain in neck ( n = 1), arms and shoulders ( n = 4) during and between training sessions, dizziness that disappeared after 5 min ( n = 1), feeling tired in the head/dizziness that disappeared after training with no other signs of autonomic hyperreflexia ( n = 2), increased spasms ( n = 2), and vomiting just after training ( n = 2).” However, as only 7 participants completed the intervention, it cannot be determined whether these events were reported for 1 or multiple participants.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, recent evidence has suggested that HIIT may be more enjoyable than moderate-intensity exercise for individuals with SCI [ 135 ], and so this form of training may offer a more time efficient and readily available alternative to moderate-intensity protocols. In the current review, a number of HIIT-based ACE, wheelchair propulsion, and FES hybrid cycling and skiing interventions demonstrated improvements in CRF [ 69 , 92 , 128 , 136 140 ]. The potential of “real-world” strategies such as virtual HIIT have also been discussed in a recent review by McMillan and colleagues [ 141 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation